Decomposition-based logic synthesis for PAL-based CPLDs - Opara, Adam; Kania, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents one concept of decomposition methods dedicated to PAL-based CPLDs. The proposed approach is an alternative to the classical one, which is based on two-level minimization of separate single-output functions. The key idea of the algorithm is to search for free blocks that could be implemented in PAL-based logic blocks containing a limited number of product terms. In order to better exploit the number of product terms, two-stage decomposition and BDD-based decomposition are to be used. In BDD-based decomposition methods, functions are represented by Reduced Ordered Binary Decision Diagrams (ROBDDs). The results of experiments prove that the proposed solution is more effective, in terms of the usage of programmable device resources, compared with the classical ones.
Keywords: decomposition; technology mapping; logic optimization; BDD; CPLD